In vitro anti-candida activity and mechanism of action of the flavonoid isolated from Praxelis clematidea against Candida albicans species - Abrahão Alves de Oliveira Filho, Heloísa Mara Batista Fernandes de Oliveira, Janiere Pereira de Sousa, Déborah Ribeiro Pessoa Meireles, Gabriela Lemos de Azevedo Maia, José Maria Barbosa Filho, José Pinto de Siqueira Júnior, Edeltrudes Oliveira Lima (Journal of Applied Pharmaceutical Science, 2016)
The prevalence of candidiasis in the world is high. Candida species are able to create superficial and systemic infections. Candida albicans is an opportunistic pathogen, causing mycoses in immunocompromised patients as well as long-term antibiotic users. The present study objective was to evaluate in vitro anti-candida effect of this compost isolated from Praxelis clematidea. The minimum inhibitory concentration (MIC) and the minimum fungicidal concentration (MFC) were determined by the broth microdilution techniques. We also investigated possible flavonoid 5,7,4´trimethoxflavone (TMF) action on cell walls (0.8 M sorbitol) and cell membranes (TMF to ergosterol binding). The MIC50 of flavonoid were 64 ðœ‡g/mL and tha MFC50 was 64 ðœ‡g/mL. Involvement with the cell wall and ergosterol binding were comproved as possible mechanisms of action. In conclusion the flavonoid showed in vitro antifungal potential against strains of C. albicans.
Keywords: Flavonoid, antifungal, Candida, Praxelis clematidea.